Procedural sedation in paediatric minor procedures: a prospective audit on ketamine use in the emergency department. Issue 3 (22nd April 2004) - Ellis, D Y; Husain, H M; Saetta, J P; Walker, T
Abstract : Objectives: To further evaluate the safety profile and efficacy of intramuscular ketamine for procedural sedation during paediatric minor procedures in the emergency department and to ascertain parental satisfaction with the treatment of their children. Methods: A prospective audit of ketamine use in a UK district general hospital involving 89 children requiring minor procedures. Children received topical anaesthesia followed by an intramuscular injection of ketamine 4 mg/kg and intramuscular atropine 0.02 mg/kg. The procedure was assessed by way of a physician completed form and by evaluation of questionnaires given to parents to gauge levels of satisfaction. Results: No child required admission to hospital and there were no serious complications. A high level of satisfaction was expressed by all the parents/guardians of the children treated. Conclusions: High levels of satisfaction among parents and staff together with the avoidance of hospital admission and improved resource management should be a sufficient incentive for hospital trusts to consider the establishment of this type of service.